Direito ao desenvolvimento socioeconômico, crise, tempo e cidadania: reflexões à luz de Kant, Rawls e Habermas - Medeiros Júnior, José Flôr de (2018)
The present dissertation aims to discuss socioeconomic development based on citizenship and freedom, through analysis of development theories and the persistence of regional and social inequalities with a focus on the theoretical elaboration of Kant, Rawls and Habermas. This, categories such as crisis, time citizenship and freedom need new reactions before the new legalpolitical-economic-social-cultural clash. Establishing the rethinking of socioeconomic development as well as the theories elaborated on the subject in order to understand the development policies designed for and by the Brazilian State. Thus, in discussing the right to socioeconomic development, we are required to speak about crisis, time, citizenship and the academic-political dilemma of those who thought theories about socioeconomic development from the substantialist paradigm. In this way, the purpose of this one is to present answers to the problem of whether or not it is possible to achieve sustainable socioeconomic development without the realization of a citizenship as a political practice, and considering the need for socioeconomic development to be thought inter- multidisciplinary, and not only mediated by the legal field, under penalty of not complying with the constitutional provision of Article 3, II of the 1988 Constitution, which is to guarantee national development. From this angle, the construction of this will be developed in the assessment of the following hypothesis: if and to what extent the non-valuation of citizenship and freedom are obstacles to the achievement of socioeconomic development and conflict with elaborate theories on socioeconomic development, ending with to preclude the applicability of the theoretical set constructed in relation to the constitutional objective described in Art. 3, II / CRFB / 88. In the layout of the chapters, the dissertation is divided into 4 (four). The re-reading of theoretical thinking on socioeconomic development will allow us to point out a new construction on the theme in order to respond to the problems presented by the theories put up to the present.